Find the quotient.
2^3 / 5^2

Question

Asked 7/5/2016 12:30:46 PM

Updated 7/5/2016 10:09:29 PM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by jeifunk [7/5/2016 10:09:29 PM]

Justinboyd365|Points 0|

Question

Asked 7/5/2016 12:30:46 PM

Updated 7/5/2016 10:09:29 PM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by jeifunk [7/5/2016 10:09:29 PM]

Rating

3

2^3 ÷ 5^2 = 8/25

Added 7/5/2016 10:09:13 PM

This answer has been confirmed as correct and helpful.

3

y^4 · y^6 = y^10

Added 7/5/2016 10:09:27 PM

This answer has been confirmed as correct and helpful.

Find the quotient.
n^12 / n^4 **Weegy:** n^12 / n^4 = n^8 **User:** Evaluate m^0 - n^2 for m = 2 and n = -1. **Weegy:** To solve this expression (m^0 - n^2), we need to know that any number raised to the power of 0 will equal 1. To solve, we first plug in the variables: 2^0 - (-1)^2. Next, we solve: 1 - 1 = 0. The solution is 0. **User:** Evaluate the following expression.
(-6)^-2 **User:** Simplify.
(-4a^3)^3·a ^4 **Weegy:** (-4a^3)^3 *a^4 = - 64a^13 **User:** Simplify.
(-3ab^3)^4 **Weegy:** (-3ab^3)^4 = 81a^4b^12 **User:** Evaluate 2x^-4 y for x = 2 and y = 4. **Weegy:** 2x - 4y for x = 2 and y = 4; 2(2) - 4(4); = 4 - 16; = -12 **User:** Find the product.
y^4 · y^6 **User:** Find the product and express your answer in scientific notation.
(3.4 x 10^-5)(5 x 10^9) (More)

Question

Updated 7/5/2016 4:30:58 PM

3 Answers/Comments

Given: X = r + 2, Y = 2r - 9, and Z = r 2 + 17r + 30.
Simplify [X · Y - Z] ÷ X.
-r - 24
r - 24
2r 2 - 6r - 33
2r 2 + 6r + 33
**Weegy:** X = r + 2, Y = 2r - 9, and Z = r^2 + 17r + 30 [X * Y - Z] / X = [(r + 2)(2r - 9) - (r^2 + 17r + 30)]/(r + 2) = (2r^2 - 9r + 4r - 18 - r^2 - 17r - 30)/(r + 2) = (r^2 - 22r - 48)/(r + 2) = (r - 24)(r + 2)/(r + 2) = r - 24 **User:** Find the product.
(6a + b) 2
12a 2 + ab + b 2
36a 2 + ab + 36b 2
36a 2 + 12ab + b 2
36a 2 + b 2
**Weegy:** (6a + b)^2 = 36a^2 + 12ab + b^2 **User:** Perform the long division and check in your notebook. Select the correct answer.
(y 3 - 125) ÷ (y - 5)
y 2 + 5y + 25
y 2 + 25
y 2 + 5y
xy 2 - 5
**Weegy:** (y^3 - 125) / (y - 5) = y^2 + 5y + 25 **User:** Find the product.
(7q - 5)(7q + 5)
49q 2 - 10q - 25
49q 2 + 10q - 25
49q 2 - 25 **Weegy:** (7q - 5)(7q + 5) = 49q^2 - 35q + 35q - 25 = 49q^2 - 25 **User:** Simplify b(a + b) - a(a - b).
a 2 + 2ab + b 2
a 2 - 2ab + b 2
-a 2 + 2ab + b 2
-a 2 - 2ab - b 2 **Weegy:** b(a + b) - a(a - b) = ab + b^2 - a^2 + ab = b^2 + 2ab - a^2 **User:** Simplify 5 + 2{x - 4[3x + 7(2 - x)]}.
-34x - 107
34x - 107
34x + 107
**Weegy:** 5 + 2{x - 4[3x + 7(2 - x)]} = 5 + 2{x - 4[3x + 14 - 7x]} = 5 + 2[x - 12x - 56 + 28x] = 5 + 2x - 24x - 112 + 56x = 34x - 107 **User:** Find the product.
-2x(x 2 - 3)
-2x 3 - 6x
-2x 3 + 6x
-2x 2 + 6x
6x 3
(More)

Question

Updated 7/12/2016 8:43:43 AM

1 Answer/Comment

32,292,997

questions answered

There are no comments.